High fibrin/fibrinogen degradation product value as a risk factor for progressive remote traumatic intracranial haemorrhage following neurosurgery. (2nd November 2021) - Sakakura, Kazuki; Ikeda, Go; Nakai, Yasunobu; Watanabe, Noriyuki; Uemura, Kazuya; Zaboronok, Alexander; Ishikawa, Eiichi; Matsumura, Akira
Abstract: Introduction: Remote traumatic intracranial haemorrhage (RTIH) may develop after neurosurgery. Recognition of the risk factors for RTIH before surgery might be of great value. The purpose of this study was to verify if the fibrin/fibrinogen degradation product (FDP) value may be a risk factor for RTIH. Methods: This was a retrospective study of the data of 56 patients with traumatic intracranial hematomas shown on initial computed tomography (CT) who were treated with craniotomy or decompressive craniectomy and underwent a follow-up CT at a single centre over a period of approximately 10.5 years. We divided the patients into 2 groups: those who developed RTIH (Positive: P-group) and those who did not (Negative: N-group). We compared the 2 groups in terms of not only the laboratory data before surgery, but also patient age, sex, antiplatelet/antithrombotic medications received, cause of injury, and GCS score on arrival. Results: RTIH was observed in 22 patients (P-group, 39.3%). The FDP value was the only significant risk factor identified in this study ( p  = 0.00076). The cut-off value was estimated on the basis of the area under the receiver operating characteristic (ROC) curve. The cut-off FDP value was 120 µg/mL (63.6% sensitivity and 85.3% specificity). Conclusions: FDP levels over 120 µg/mL were determined to be a risk factor for progressive RTIH after neurosurgery. We suggest the FDP level be checked before surgery for traumatic intracranial haemorrhage and follow-up CT be done as soon as possible after the surgery if the serum FDP level is over 120 µg/mL.